1984
DOI: 10.1016/0014-5793(84)80822-4
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue in the parametrial fat pad of the mouse

Abstract: Cold acclimation has been shown to produce a substantial increase in the number of brown adipocytes in the parametrial fat pad of female BALB/c mice ‐ a site normally thought to consist of typical white adipocytes. The brown adipocytes have been identified not only on the basis of their morphology using light and electron microscopy, but also on the basis of the content of the mitochondrial ‘uncoupling protein’ (M r = 32 000) which is characteristic of the proton conductance pathway of brown adipose tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
240
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(247 citation statements)
references
References 15 publications
4
240
0
3
Order By: Relevance
“…Previous studies found brown fat emergence in WAT coupled with enhanced whole-body energy expenditure, but these studies used non-dietary manipulations, including chronic exposure to cold, treatment with b3-adrenergic receptor agonists and forced WAT overexpression of key molecules of brown fat adipogenesis/function, such as PGC-1a, UCP1 or PRDM16. 12,14,18,20,[39][40][41][42] Brown fat adipogenesis has recently gained the interest of many research groups, as compelling evidence has been provided that brown fat exists not only in human neonates, as thought originally, but also in human adults where it likely protects against obesity, 2-8 through its superior capacity for burning fat (both stored and eaten) and energy dissipation. 9,43 Substantial progress in our understanding of brown fat adipogenesis has been made recently (Seale et al 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found brown fat emergence in WAT coupled with enhanced whole-body energy expenditure, but these studies used non-dietary manipulations, including chronic exposure to cold, treatment with b3-adrenergic receptor agonists and forced WAT overexpression of key molecules of brown fat adipogenesis/function, such as PGC-1a, UCP1 or PRDM16. 12,14,18,20,[39][40][41][42] Brown fat adipogenesis has recently gained the interest of many research groups, as compelling evidence has been provided that brown fat exists not only in human neonates, as thought originally, but also in human adults where it likely protects against obesity, 2-8 through its superior capacity for burning fat (both stored and eaten) and energy dissipation. 9,43 Substantial progress in our understanding of brown fat adipogenesis has been made recently (Seale et al 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…11 The first use of the term 'beige', to our knowledge, was by the Seale laboratory 12 in a commentary about a paper by Vegiopoulos et al 13 The first reports of the presence of 'brown adipocytes' among white adipocytes in traditionally white adipocyte depots to our knowledge, however, occurred 26 years earlier in the pioneering studies of Young et al 14 They reported brown adipocytes in the parametrial WAT pad of BALB/c mice acclimated to the cold, as identified morphologically by light and electron microscopy, and as possessing increases in a marker of brown adipocytes, mitochondrial UCP-1 content, 14 the finding of which the field and we turned a blind eye toward because such a presence was almost heretical, given the Zeitgeist of the time that WAT and BAT were separate tissues with separate functions. Loncar et al 15 soon after reported that young (10-13 weeks old) domestic cats exposed to − 30°C for 1 h twice a day during a week displayed brown-like adipocyte changes, most notably increases in mitochondria volume and surface density of mitochondrial cristae in several WAT depots not seen in the room temperature controls and more typical of brown adipocytes, not white ones.…”
Section: Methodsmentioning
confidence: 99%
“…UCP1 is usually only expressed in significant amounts in BAT and not in WAT, so that the appearance of this protein in WAT is considered as a sign of a transdifferentiation process, that is, the conversion of WAT in a tissue with cellular similarities to BAT. Acquirement of BAT-like features by WAT can be provoked by physiological conditions, such as cold stress, 22 or by pharmacological intervention, such as b 3 -adrenergic stimulation. 23 Moreover, UCP1 expression in WAT is related to body weight loss in obese and UCP1 transgenic mice 24,25 and can also occur in human white adipocytes.…”
Section: Effect Of C18 Fatty Acids On Body Weight O Vögler Et Almentioning
confidence: 99%